Impact of Knack Manoeuvre Among Women with Urinary Incontinence: A Quasi Experimental Study - J Jagadeeswari; S. Kalabarathi; G. Bhuvaneswari (Wolters Kluwer Medknow Publications, 2024)
Objective: The Objective of the study is to assess the effectiveness of Knack manoeuvre among women with urinary incontinence. Methods: A quasi-experimental study with a repeated measures design was used to conduct study at Saveetha Medical College Hospital. Experimental group received Knack manoeuvre for 6 months and control group received routine care. The sample size was 100, which was recruited by purposive sampling technique. The data were collected with structured questionnaire, and questionnaire for urinary incontinence diagnosis and biophysiological parameters were assessed by abdominal leak peak pressure (ALPP). Results: The study results depict that frequency and percentage distribution of pretest and post-test level of ALPP. Between group comparison of post-test at 6 months of control and experimental showed significance (P < 0.001). There was a progressive decrease in ALPP of control and experimental groups. Conclusion: To our knowledge, this is the first prospective nonrandomized study that assesses the efficacy of the Knack manoeuvre on urine incontinence by assessing biophysiological parameters.